Crop residue managementAn approach to transforming waste into health - Sahu, Raghubar; Sohane, R K; Kumar, Rakesh (Indian Farming, 2024)
Sustainable agriculture and related industries are necessary to promote human prosperity since they directly or indirectly employ 82% of the world's workforce and provide the foundation of economies in many developed and developing countries. Reducing agriculture dependence on resources is one of the most crucial strategies for ensuring sustainable food production. Resource saving farming practices are essential to a sustainable food production system. Input-intensive farming practices usually result in a major loss of soil nutrients and increased usage of modern heavy agricultural machinery such as combine harvesters and rotavators. In the rice-wheat system and in the Indian subcontinent, the usage of combine harvesters and seed-cum-fertilizer drills has increased significantly in recent years. Crop residue production increased linearly because of contemporary input intensive farming techniques. Farmers usually burn these crop residues on-site, which is harmful to the environment. Crop residue burning poses a serious risk to the health of people and the environment. Asia burns more than one-third of its entire biomass as in-situ agricultural residue, according to research. Furthermore, burning produces particulates like PM10/PM2.5 as well as GHGs, which add to pollution in atmosphere.